Kesembuhan Ilahi dalam Khotbah: Analisis tentang Otoritas Spiritual Kaum Karismatik - Walean, Rudy Roberto (Sekolah Tinggi Teologi Mawar Saron Lampung, 2026)
Divine healing in preaching represents a complex and dynamic expression of spiritual authority. The spiritual authority of charismatics derives not only from hierarchical positions but also from personal experience, biblical interpretation, and the recognition of spiritual gifts. This study aims to comprehensively analyze how narratives of divine healing in preaching construct, affirm, and validate the spiritual authority of charismatic leaders in Indonesia. This research is relevant because divine healing is a central element in charismatic religious practice, while also offering a unique perspective on the construction of authority and contemporary spiritual experience. Utilizing a qualitative approach and literature study, this research identifies key patterns in sermon narratives, congregational responses, and theological interpretations related to divine healing. The findings indicate that spiritual authority in divine healing sermons is built through claims of anointing, demonstrations of spiritual gifts, the use of persuasive rhetoric, and personal testimonies that function as empirical validation. This authority is subsequently reinforced through the faithful response and active participation of the congregation in healing rituals. This study concludes that divine healing in charismatic preaching is a multidimensional phenomenon encompassing theological, spiritual, and sociological dimensions. This practice not only shapes the authority of leaders but also strengthens the cohesion of the faith community through shared spiritual experience.